The Konov nesting of enveloping algebra into the ring with divisions - Wehrfritz , В. A. F. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
In 1961 Р. М. Cohn proved that the universal enveloping algebra of any Lie algebra over a field-can be embedded into a division ring. (The Lie algebra is not assumed to be finite dimensional.) Cohn’s method is less than direct. We give a more explicit construction. These division rings have recently found uses in the theory of skew linear groups.